Auranofin/Vitamin C: A Novel Drug Combination Targeting Triple-Negative Breast Cancer. (20th November 2018) - Hatem, Elie; Azzi, Sandy; El Banna, Nadine; He, Tiantian; Heneman-Masurel, Amélie; Vernis, Laurence; Baïlle, Dorothée; Masson, Vanessa; Dingli, Florent; Loew, Damarys; Azzarone, Bruno; Eid, Pierre; et al.
Abstract: Background: Cancer cells from different origins exhibit various basal redox statuses and thus respond differently to intrinsic or extrinsic oxidative stress. These intricate characteristics condition the success of redox-based anticancer therapies that capitalize on the ability of reactive oxygen species to achieve selective and efficient cancer cell killing. Methods: Redox biology methods, stable isotope labeling by amino acids in cell culture (SILAC)-based proteomics, and bioinformatics pattern comparisons were used to decipher the underlying mechanisms for differential response of lung and breast cancer cell models to redox-modulating molecule auranofin (AUF) and to combinations of AUF and vitamin C (VC). The in vivo effect of AUF, VC, and two AUF/VC combinations on mice bearing MDA-MB-231 xenografts (n = 5 mice per group) was also evaluated. All statistical tests were two-sided. Results: AUF targeted simultaneously the thioredoxin and glutathione antioxidant systems. AUF/VC combinations exerted a synergistic and hydrogen peroxide (H2 O2 )-mediated cytotoxicity toward MDA-MB-231 cells and other breast cancer cell lines. The anticancer potential of AUF/VC combinations was validated in vivo on MDA-MB-231 xenografts in mice without notable side effects. On day 14 of treatments, mean (SD) tumor volumes for the vehicle-treated control group and the two AUF/VC combination–treated groups (A/V1 and A/V2) were 197.67 (24.28) mm 3, 15.66 (10.90) mm 3, and 10.23 (7.30)mm 3, respectively; adjusted P values of the differences between mean tumor volumes of vehicle vs A/V1 groups and vehicle vs A/V2 groups were both less than .001. SILAC proteomics, bioinformatics analysis, and functional experiments linked prostaglandin reductase 1 (PTGR1) expression levels with breast cancer cell sensitivity to AUF/VC combinations. Conclusion: The combination of AUF and VC, two commonly available drugs, could be efficient against triple-negative breast cancer and potentially other cancers with similar redox properties and PTGR1 expression levels. The redox-based anticancer activity of this combination and the discriminatory potential of PTGR1 expression are worth further assessment in preclinical and clinical studies.